ASSESSMENTS ON THE ECONOMIC AND FISCAL DIMENSIONS OF THE OLYMPICS IN THE FRAMEWORK OF THE WHITE ELEPHANT SYNDROME (Third Sector Social Economic Review, 2023)
Under the chairmanship of Pierre de Coubertin, International Olympic Committee was established in Paris in 1894. 14 countries were represented in First Olympics in Athens 1896. After first Olympics with 9 sports branches, number of branches and competitions increased and Tokyo 2020 Olympics witnessed 339 medal struggles in 33 branches. Beijing 2008 was the highest-cost Olympics with expenditures $42 billion. Olympics started as sports organization, mean more than sports organization with budgets, economy, tv broadcasts, sponsorships, tourism. Countries organize the Olympics make significant infrastructure expenditures and investments for stadiums. This makes economic dimension of games as remarkable as sportive dimension. Risk of investment projects remaining idle after the games, opens up the costs of Olympics to discussion. Investments, stadiums, their financing, and the fact that these projects cannot be actively evaluated after the games bring about evaluations in the literature on Olympics, especially within the framework of ""white elephant syndrome"". Study focuses Rio 2016, London 2012, Beijing 2008, Athens 2004 Olympics, and deals with the economic and financial dimensions of Olympics within the framework of white elephant syndrome. Olympics are examined in light of economic, financial and sportive data and discussed in terms of costs and gains from Olympics.
Keywords: Olympics; White Elephant Syndrome; Public Finance; Sport Centers; Investments